Structural and Functional Alterations in Betel-Quid Chewers: A Systematic Review of Neuroimaging Findings - Sariah, Adellah; Liu, Zhening; Pu, Weidan; Liu, Haihong; Xue, Zhimin; Huang, Xiaojun (Frontiers in Psychiatry, 2019)
Abstract Background A number of neuroimaging studies have been conducted to investigate structural and functional changes in betel quid (BQ) chewers. We present a systematic review of neuroimaging studies with emphasis on brain structural and functional connectivity alterations resulting from BQ chewing. Methods All BQ neuroimaging studies were identified by searching PubMed, EMBASE, and Google scholar for English articles published until March 2018 using the key words: Betel-quid, resting state, functional MRI, structural MRI, diffusion tensor imaging (DTI) and betel quid dependence basing on the PRISMA criteria. Unpublished studies were also sought. The rest were obtained from reference lists of the retrieved articles. All neuroimaging studies investigating brain structure and function alteration with regard to BQ chewing and BQ dependence were included. Our systematic review registered is CRD42018092669. Results A review of 12 studies including 7 resting-state fMRI, and 5 structural MRI which met the established inclusion criteria showed that BQ chewers and BQ dependent individuals have increased functional connectivity (FC) changes in precuneus, hippocampus, orbitalfrontal, frontotemporal, occipital/parietal, occipital/temporal/cerebellum, limbic networks, and midbrain regions; while, some prefrontal cortex (PFC) regions, insula, parahippocampal/hypothalamus, and anterior default mode network had decreased FC. Increased grey matter volume (GMV) was found in right hippocampal and precuneus; while, reduced GMV was detected in midbrain, some the PFC regions, and rSTG. Increased factional anisotropy (FA) was reported in ACC, midbrain, rSTG, parietal lobe, angular, occipital, and central gyrus regions; parietal lobe, while, a decrease was seen in anterior thalamic radiation (ATR). BQ duration and severity of betel quid dependence were linked with majority of structural and functional alterations in BQ chewers and BQ dependent individuals. Conclusion Betel quid chewing and dependence is associated with brain alterations in structure, and function which are greatly influenced by duration and severity of betel quid dependence. Future longitudinal neuroimaging studies are required to demonstrate a cause and effect relationship among brain alterations and their neuro-mechanisms with regard to betel quid chewing and its dependence.